Language teacher development in digital contexts - Kayi-Aydar, Hayriye; Reinhardt, Jonathon (Language learning and language teaching, 2022)
"This volume demonstrates how various methodologies and tools have been used to analyze the multidimensional, dynamic, and complex nature of identities and professional development of language teachers in digital contexts that have not been adequately examined before. It therefore offers new understandings and conceptualizations of language teacher development and learning in varied digital environments. The collection of pieces illustrates a field that is recognizing that digital environments are the contexts of teacher learning, not simply the object of it, and that issues of identity and agency are central to that learning. As an excellent resource on digital technologies, CALL, gaming, or language teacher identity and agency, the book can be used as a textbook in various applied linguistics courses and graduate seminars"--